2018
DOI: 10.4142/jvs.2018.19.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, toxin gene profile, antibiotic resistance, and molecular characterization ofClostridium perfringensfrom diarrheic and non-diarrheic dogs in Korea

Abstract: Clostridium perfringens causes diarrhea and other diseases in animals and humans. We investigated the prevalence, toxin gene profiles, and antibiotic resistance of C. perfringens isolated from diarrheic dogs (DD) and non-diarrheic dogs (ND) in two animal hospitals in Seoul, Korea. Fecal samples were collected from clinically DD (n = 49) and ND (n = 34). C. perfringens was isolated from 31 of 49 DD (63.3%) and 21 of 34 ND dogs (61.8%). All C. perfringens strains were positive for the α toxin gene, but not for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Both C. perfringens enterotoxin and cpe are more commonly detected in dogs with diarrhea than in non‐diarrheic dogs . Similarly, the cpb2 gene recently was identified in a larger number of C. perfringens isolates from diarrheic dogs as compared to non‐diarrheic dogs . Additional C. perfringens genes and associated toxins also seem to be involved in specific forms of disease such as acute hemorrhagic diarrhea syndrome .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both C. perfringens enterotoxin and cpe are more commonly detected in dogs with diarrhea than in non‐diarrheic dogs . Similarly, the cpb2 gene recently was identified in a larger number of C. perfringens isolates from diarrheic dogs as compared to non‐diarrheic dogs . Additional C. perfringens genes and associated toxins also seem to be involved in specific forms of disease such as acute hemorrhagic diarrhea syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Although C. perfringens and its toxins often are associated with acute diarrhea, it is still unclear if this bacteria is a cause or consequence of the intestinal disease . We did not evaluate C. perfringens in a healthy population of dogs, but previous studies have shown that isolation rates are similar in diarrheic and non‐diarrheic dogs, and the C. perfringens toxins associated with diarrhea also can be identified in healthy, non‐diarrheic dogs . Further complicating matters, the presence of toxin‐encoding genes does not always correlate to the presence of actual toxins .…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium perfringens is also a pathogenic bacterium that may come from contaminated food and causes gastrointestinal infections mediated by toxins release. Resistance of C. perfringens was developed to antibiotics that are used in farms such as streptomycin, lincomycin, trimethoprim-sulfamethoxazole, with lower resistance percentage to ciprofloxacin, cefotaxime, and rifampicin [54,55].…”
Section: Other Resistant Gram-positive Bacteriamentioning
confidence: 99%
“…The CP isolates were maintained in BHI broth with 20% glycerol and stored at −70°C until use. Isolates were grown in the Whitley DG250 Anaerobic Workstation (Don Whitley Scientific Ltd., Shipley, UK) at 37°C with a gas mixture of 90% N 2 , 5% H 2 , and 5% CO 2 as previously described ( Chon et al., 2018 ). CP KJW-1 ( CJ17 ) among the 45 clinical isolates ( Supplementary Table 1 ) was selected as a challenge strain, and a small-scale pilot study confirmed its pathogenicity for inducing NE in broilers (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Clostridium perfringens strains, including CJ17 used for CP challenge, were recovered ( Chon et al., 2018 ) and counted using the culture-based method. On day 17 and 18, ∼3 cm to ∼5 cm of ileal and cecal tissues from 6 chicks of each group were collected, stored on ice, and moved to the laboratory within 4 h after collecting samples.…”
Section: Methodsmentioning
confidence: 99%